Automatic voting counter system by using Arduino / Muhammad Amin Azhar and Muhammad Asyraf Muhammad Zaidi - Azhar, Muhammad Amin; Muhammad Zaidi, Muhammad Asyraf (2019)
In a campus, an election is one of the most important things for students to do to appoint their new leader for the campus organization. The leader is chosen by counting the most votes received from the voter. However, problems often occur regarding the counting vote process such as took a long time to finish counting and too many fake votes received, for example in a certain campus votes are often received by the same person although they already know that they can only vote once in an election. To overcome these problems, one of the easiest ways to improve counting vote process is by using an automatic vote system. It uses a Tcs230 color sensor detection of votes which sets in red, blue and green color. Voters get to choose the color of vote they want and put it in the voting box. Votes counting process will be much easier to be done and saves time. Not to mention, the number of each color vote will be displayed on the LCD and make it easier for the counters to see the results. So, the election will be finished way faster using this method rather than the manual vote counting. This can be seen clearly when manual vote counting can sometimes lead to miscalculation and of course immediate recounting need to be done from the beginning which can be tiring and waste a lot of time.